Severe hypoglycemia in patients with liver cirrhosis and type 2 diabetes - Yen, Fu-Shun; Hou, Ming-Chih; Liu, Jia-Sin; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Medicine, 2023)
Advanced liver disease with massive liver damage may affect the metabolism of hypoglycemic agents and increase the risk of hypoglycemia. We conduct this study to compare the risk of severe hypoglycemia between patients with type 2 diabetes (T2D), with and without compensated liver cirrhosis. From Taiwan’s National Health Insurance Research Database (NHIRD), we identified patients with T2D with cirrhosis (n= 18209) and without cirrhosis (n = 538510) from January 1, 2000, to December 31, 2010. Cox proportional hazards models were used to assess risks of all-cause mortality and severe hypoglycemia. The mean follow-up time of this study was 3.7 years. The incidence rates of mortality during follow-up were 26.54 and 2.75 per 1000 patient-years [aHR 7.63 (6.70-8.70)] for patients with cirrhosis and without cirrhosis, respectively. The incidence rates of severe hypoglycemia during follow-up were 0.53 and 0.14 per 1000 patient-years [aHR 2.74 (1.52-4.92)] for patients with and without cirrhosis, respectively. The subgroup analysis of hypoglycemia risks in patients with and without cirrhosis disclosed no significant interaction for variables such as age, sex, chronic kidney disease (CKD), sulfonylurea (SU) use, number of oral antidiabetic drugs, insulin, β-blocker, and fibrate. This cohort study demonstrated that patients with T2D and compensated liver cirrhosis showed higher risks of mortality and severe hypoglycemia than those without liver cirrhosis.